2017
DOI: 10.1002/nau.23331
|View full text |Cite
|
Sign up to set email alerts
|

A populational—based survey on the prevalence, incidence, and risk factors of urinary incontinence in older adults—results from the “SABE STUDY”

Abstract: Aims: To estimate the prevalence and incidence of urinary incontinence (UI) and identify the associated risk factors in a cohort of elderly individuals in Brazil. Methods: In 2006, individuals aged ≥60 years were selected from the SABE Study (Health, Well-being, and Aging). The dependent variable was reported UI in 2009. UI was assessed using the International Consultation on Incontinence Questionnaire Urinary Incontinence-Short Form (ICIQ-UI SF). Incidence was measured in units of 1000 person-years, and Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
2
17
1
9
Order By: Relevance
“…This study does not involve longitudinal followup and these results are likely to be the fruits of reverse causality, as while it is difficult to say that UI causes functional disability, the opposite can be stated 6,8,11,14,16,18 . One study 25 justifies this result by stating that incontinent women reduce physical activity due to fear of accidental urine loss and, consequently, there is an increase in functional limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study does not involve longitudinal followup and these results are likely to be the fruits of reverse causality, as while it is difficult to say that UI causes functional disability, the opposite can be stated 6,8,11,14,16,18 . One study 25 justifies this result by stating that incontinent women reduce physical activity due to fear of accidental urine loss and, consequently, there is an increase in functional limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized literature shows that the factors associated with its occurrence are: the female gender and advanced age [6][7][8] , non-Caucasian ethnicity 9 and the lack of or low levels of schooling [8][9][10] . Studies have shown UI as associated with diseases such as: infection of the urinary tract 11 , arterial hypertension 12 , diabetes mellitus 6,[12][13][14] , a history of cardiac disease 4 , obesity 4,6,10 , strokes 6,8,13,15 , respiratory problems 8,15 , depression 6 , cognitive deficit 16 , arthritis 12 , arthrosis/rheumatism 17 , prostatic hyperplasia 18 , a history of falls 4,17 , functional limitations, limited mobility or dependence 6,8,11,14,16,18 , comorbidity 19 and frailty 17 . in addition to these conditions, UI may be associated with lifestyle habits such as sedentiarism 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta investigação é parte integrante do estudo SABE (Saúde, Bem-estar e Envelhecimento) e caracteriza-se como uma pesquisa epidemiológica transversal, com amostra de base populacional. [18][19][20] . Ressalta-se que, em 2010, a população de idosos residentes no Município de São Paulo era de 1.338.138 indivíduos 21 .…”
Section: Métodounclassified
“…A Incontinência Urinária (IU) é definida como qualquer perda involuntária de urina (Haylen et al, 2010) e a sua maior ocorrência ocorre no sexo feminino (28,2%) (Tamanini, 2017) e com o aumento da idade (Marques et al, 2015). Sabese que o treinamento dos músculos do assoalho pélvico (TMAP) é fortemente recomendado para o tratamento da IU (Dumoulin et al, 2016).…”
Section: Introductionunclassified